Financial management and product marketing training for the Program Keluarga Harapan Groups - Puspita, Wulan Dri; Rahayu, Dewi Ayu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The managing of Hope Family Program or Program Keluarga Harapan (PKH) is the supervisor of the business unit in the form of electronic warung gotong royong (e-Warong) which is a social assistance program to synergies between PKH and the Joint Venture Group or Kelompok Usaha Bersama (KUBE). PKH of Bantur’s subdistrict experienced several problems related to financial management for their business activities, especially their inventory recording and they were not aware to promote through marketplaces. Therefore by the program of community service the University of Merdeka  Malang, PKH Bantur’s subdistrict was expected to be able to gain an understanding of inventory recording and marketing to solve their problems by using google forms, google spreadsheet, and Shopee. There are three methods for these activities: lectures, practices, and discussions. These activities are divided into two sessions. The first session was introducing the importance of financial management, inventory management, and the use of google form and google spreadsheet. The second session explained digital marketing and the use of Shopee. The participants looked enthusiastic during the event. Through these activities, participants can understand the importance of managing inventory, the benefits of google form and google spreadsheets to control their inventory, also they can use Shopee as marketing media to gain more income.